Medication Use, Service Utilization, and Medical Costs Associated With New Episodes of Bipolar Disorder: Evidence From a Retrospective Claims Database - Ohsfeldt, Robert L. (Physicians Postgraduate Press, Inc., 2007)
Objective: To identify resource use patterns and costs incurred during new episodes of bipolar disorder. Method: Researchers examined Medstat MarketScan databases covering the interval of January 1, 1998, to December 31, 2002, to identify 6148 patients with new episodes of bipolar disorder as defined by the International Classification of Diseases, Ninth Revision. Resource utilization patterns and costs for the 6 months prior to the index date and for the 30 days and 1 year after the index date were examined. Differences among subcategories of bipolar patients in terms of the resources used before and after the index date were also examined. Results: The majority of the individuals in the study were female (61.3%) and the mean age was 41.9 years. Patients diagnosed as manic had higher bipolar treatment costs (p < .01) and were more likely to be hospitalized for mental health diagnoses 30 days (p < .01) and 1 year after the index diagnosis (p = .02) compared with individuals diagnosed as depressive, mixed, or other/ unknown. Median total medical costs in the 1 year after the index date were highest for those diagnosed as depressed (p = .02), while patients diagnosed as mixed bipolar had significantly more psychiatrist visits after the index date (p < .01). Approximately 15% of patients were not treated with any central nervous system medication, and over 50% of patients were treated with antidepressants. Conclusion: The subcategory of bipolar disorder that an individual is diagnosed as having significantly affects resource use and costs after such diagnosis. Patients diagnosed as manic generally used more resources than other individuals. In addition, results suggest that a large proportion of individuals are not being treated in accordance with recommended treatment guidelines.